2018
DOI: 10.1186/s12889-018-5851-5
|View full text |Cite|
|
Sign up to set email alerts
|

Association between internal migration and epidemic dynamics: an analysis of cause-specific mortality in Kenya and South Africa using health and demographic surveillance data

Abstract: BackgroundMany low- and middle-income countries are facing a double burden of disease with persisting high levels of infectious disease, and an increasing prevalence of non-communicable disease (NCD). Within these settings, complex processes and transitions concerning health and population are underway, altering population dynamics and patterns of disease. Understanding the mechanisms through which changing socioeconomic and environmental contexts may influence health is central to developing appropriate publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…It is not illuminated by the South African national census, which gives a snapshot of where people reside on census night. Many single-person or small households enumerated in urban settings are likely to be members of rural households situated elsewhere, to which they will return in times of leave or ill-health [ 24 , 58 ]. The high prevalence of temporary migration from rural households in northeast South Africa, especially for young adults, illustrated with respect to the Agincourt HDSS population, reflects a typical pattern for rural Southern Africa, yet this population remains less visible and their health challenges insufficiently understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not illuminated by the South African national census, which gives a snapshot of where people reside on census night. Many single-person or small households enumerated in urban settings are likely to be members of rural households situated elsewhere, to which they will return in times of leave or ill-health [ 24 , 58 ]. The high prevalence of temporary migration from rural households in northeast South Africa, especially for young adults, illustrated with respect to the Agincourt HDSS population, reflects a typical pattern for rural Southern Africa, yet this population remains less visible and their health challenges insufficiently understood.…”
Section: Discussionmentioning
confidence: 99%
“…South Africa’s internal migrants have a significantly higher burden of HIV compared with non-migrants and are at higher risk of HIV acquisition [ 22 , 23 ]. A longitudinal study of premature mortality among internal migrants from the African Health Research Institute and the Agincourt Health and Demographic Surveillance Systems (HDSS) revealed that return migrants to these HDSS areas had a four times higher risk of mortality from AIDS/TB and NCD as compared with permanent residents, suggesting a marked mortality disadvantage among migrants [ 24 ]. Whether suffering from a non-communicable or infectious disease (or increasingly both), individuals with chronic conditions require ongoing treatment and regular medical follow-up [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between migration and health is found to be multidimensional and bidirectional. Health status can drive a decision to migrate, but such relocation may in turn have an influence on health (Ginsburg et al, 2018). Circular migration has further been associated with the spread of health conditions or behaviours between destination and origin areas, affecting the health status of others.…”
Section: Introductionmentioning
confidence: 99%
“…The well-known Cox model (semi-parametric proportional hazard model is its full name) and the less known Fine and Gray model for non-independent competing risks [11] can easily be implemented using the same micro data that we used to produce rates and probabilities. The MADIMAH team has successfully applied these methods to analyses of determinants and outcomes of demographic processes, to produce results that are comparable across diverse settings [12, 13].…”
Section: Resultsmentioning
confidence: 99%